Chemical dynamics underpinning the compounded sequence and spatiotemporal topology controls in Lewis pair polymerization - Reilly, Liam T., author; Chen, Eugene Y.-X., advisor; Miyake, Garret M., committee member; Crans, Debbie C., committee member; Radford, Donald W., committee member (Colorado State University. Libraries, 2025)
Lewis Pair Polymerization (LPP) has emerged as a uniquely versatile platform for precision polymer synthesis. In particular, LPP's ability to regulate polymer comonomer sequence and topology sets it apart from alternative methodologies. This contribution unravels the chemical dynamics and mechanisms of control that underpin LPP's most unique capabilities. Specifically, this work elucidates the interplay of the kinetic and thermodynamic biases that arise within comonomer mixtures and demonstrates how this fundamental knowledge can be used to prepare advanced materials. Likewise, this work dissects the dynamic origin of LPP's spatiotemporal control and leverages these findings to develop a new route to access traditionally elusive polymers of advanced topology. Collectively, these efforts serve as an example of how fundamental research can lead to new frontiers in materials design and discovery.
Keywords: Lewis pair polymerization; polymers; topological control; polymerization; chemical dynamics; topological characterization